2020
DOI: 10.3390/nu12061864
|View full text |Cite
|
Sign up to set email alerts
|

Role of Minerals and Trace Elements in Diabetes and Insulin Resistance

Abstract: Minerals and trace elements are micronutrients that are essential to the human body but present only in traceable amounts. Nonetheless, they exhibit well-defined biochemical functions. Deficiencies in these micronutrients are related to widespread human health problems. This review article is focused on some of these minerals and trace element deficiencies and their consequences in diabetes and insulin resistance. The levels of trace elements vary considerably among different populations, contingent on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
175
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(192 citation statements)
references
References 123 publications
6
175
0
11
Order By: Relevance
“…[ 10 , 22 ]. Similarly, oral Zn supplementation could not improve diabetic neuropathy, oxidative stress, or vascular function in patients with type 2 diabetes [ 23 , 24 ]. Additionally, studies related to Zn and MetS are scarce and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 22 ]. Similarly, oral Zn supplementation could not improve diabetic neuropathy, oxidative stress, or vascular function in patients with type 2 diabetes [ 23 , 24 ]. Additionally, studies related to Zn and MetS are scarce and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the associations of cobalt with IR and type 2 diabetes. The review by Dubey et al summarized existing research on cobalt concentrations in diabetic patients; however, there is not enough research currently, and the existing research has produced inconsistent conclusions [20]. Cao et al found that elevated or decreased plasma cobalt levels were associated with a high risk of type 2 diabetes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance of Zn homeostasis is related to various disorders. Its role in metabolic syndrome and diabetic implications has been discussed in detail [ 116 , 117 ]. Enzymes involved in cell membrane stabilization or required for metabolism of neurotransmitters, melatonin [ 118 ] and prostaglandins are using zinc as cofactor.…”
Section: Zinc (Zn)mentioning
confidence: 99%